Experiences of Thai individuals awaiting coronary artery bypass grafting: A qualitative study - Indratula R. (2014)
This qualitative descriptive study, underpinned by the naturalistic inquiry, explored the lived experiences of individuals awaiting coronary artery bypass grafting in Thailand. Eleven northern Thai individuals volunteered to participate. Data were gathered through in-depth interviews and analyzed using content analysis. Two major themes arose: uncertainty of life and striving to balance well-being. The first of these themes is presented in this paper. Uncertainty of life was recognized as a dynamic emotional state of being unsure or insecure in life, but its occurrence depended on the individual situation; it was described through two subthemes that had a profound effect on the participants: fear of death and fear of disability. Participants' uncertainty of life encompassed being unsure about the risks of dying from illness, both prior to and following the surgery, and surviving the surgery with a disability. These findings provide insight into the experiences of individuals awaiting coronary artery bypass grafting and will assist nurses and other healthcare providers in creating timely programs and appropriate interventions to reduce uncertainty of life while awaiting surgery. © 2013 Wiley Publishing Asia Pty Ltd.